Teacher’s Communication Strategies in The 3A Teenager Class of a Language Center in Surabaya - Cristian Rinanta Polii; Julia Eka Rini (Institute of Research and Community Outreach - Petra Christian University, 2025)
This study aims to find out the types of communication strategies and the reasons why the teacher uses communication strategies in the 3A teenager class of a language center in Surabaya. This study used a qualitative approach with a direct observation and an interview as data collection techniques. This study uses the theory of communication strategies by Mariani (2010) which divides communication strategies into five types: meaning-expression, meaning-negotiation, conversation-management, para- and extra-linguistic, and interaction-monitoring. The last one is not used by the teacher. The result of the interview with the teacher show that the communication strategies used in the class observation is in line with the interview, namely: to help students better understand the material, ensure students' understanding of the material, keep the flow of learning interactions structured and efficient, and as a tool for teachers to communicate non-verbally.